Correlatos psicossociais e contextuais da propensão à violência contra a mulher em relacionamentos íntimos - Biermann, Mariana Costa (2020)
The present study aimed to understand the influence of psychosocial and contextual variables as fundamental factors for the proclivity to violence against women in intimate relationships. Specifically, the correlated variables used were: ambivalent sexism (hostile and benevolent), intolerance to frustration, levels of aggression, and sociodemographic variables. Secondarily, the objective was to propose a scale to measure the proclivity to violence against women in intimate relationships and to validate a scale of discomfort to frustration. In order to achieve the proposed objective, the dissertation presents two empirical studies. Study 1 aimed to validate the scales necessary to carry out the research, focusing on the construction of a scale of proclivity to violence against women in intimate relationships and the adaptation of the Frustration Discomfort Scale for Brazil. Study 2 aimed to evaluate the relationship and the predictive value of variables related to the phenomenon addressed. Regarding the samples used, study 1 included 200 men from the general population between 18 and 78 years old (M = 29.85; SD = 12.59), with 95.4% of the participants being heterosexual and 4.6% bisexual; while study 2 included a sample of 242 men from the general population aged 18 to 60 years (M = 28.58; SD = 9.18), 96.2% heterosexual and 3.8% bisexual. Both samples were of convenience, not probabilistic, and the participation was conditioned to the signing of the Free and Informed Consent Form. Study 1 participants responded to a booklet composed of the Brazilian Version of the Frustration Discomfort Scale, the Buss-Perry Aggression Questionnaire, the Violence Propensity Scale Women in Intimate Relationships, and a sociodemographic questionnaire; and the participants of the study 2 responded to the instruments validated in study 1, the Ambivalent Sexism Inventory, as well as the sociodemographic questions. Descriptive statistical analyzes, exploratory factor analysis, Pearson's correlations, chi-square and Student's t tests, and multiple linear regressions were performed. The SPSS software (version 20) was used for this, as well as the PROCESS macro utilitary to test moderation models. The results of study 1 indicated factorial structures consistent on both scales, as well as the adequacy to the psychometric parameters of validity and precision. Regarding study 2, there was no predictive potential of discomfort to frustration in relation to violence against women in intimate relationships, diverging from the literature; however, ambivalent and hostile sexism was confirmed as predictors. Despite the existence of limitations in the present study, it is emphasized that the objectives were achieved and that significant results were systematized about the relationship between violence against women in intimate relationships and psychosocial variables in the Brazilian context.